#cos^2x+cos^2(3x)=1#
Subtract #cos^2x# from both sides
#cos^2(3x)=1-cos^2x#
Using the Pythagorean Identity #sin^2theta+cos^2theta=1#,
#1-cos^2x=sin^2x#, therefore
#cos^2(3x)=sin^2x#
Subtract #sin^2x# from both sides
#cos^2(3x)-sin^2x=0#
Factor the left side using the difference of squares
#(cos(3x)+sinx)(cos(3x)-sinx)=0#
Time to find the value of #x#
Case 1: #cos(3x)+sinx=0#
Subtract #sinx# from both sides
#cos(3x)="-"sinx#
Since #"-"sintheta=sin("-"theta)#,
#"-"sinx=sin("-"x)#, therefore
#cos(3x)=sin("-"x)#
Since #sintheta=cos(pi/2-theta)# and #cos(theta)=cos(theta+2npi),ninZZ#,
#sin("-"x)=cos(pi/2+x+2npi)#, therefore
#cos(3x)=cos(pi/2+x+2npi)#
Since #costheta=cos("-"theta)#,
#3x=pi/2+x+2npi or 3x=("-"pi)/2-x-2npi#
Case 1.1: #3x=pi/2+x+2npi#
Subtract #x# from both sides
#2x=pi/2+2npi#
Divide both sides by #2#
#color(blue)(x=pi/4+npi,ninZZ)#
Case 1.2: #3x=("-"pi)/2-x-2npi#
Add #x# to both sides
#4x=("-"pi)/2-2npi#
Divide both sides by #4#
#color(blue)(x=("-"pi)/8-(npi)/2,ninZZ)#
Case 2: #cos(3x)-sinx=0#
Add #sinx# to both sides
#cos(3x)=sinx#
Since #sintheta=cos(pi/2-theta)# and #cos(theta)=cos(theta+2npi),ninZZ#,
#sinx=cos(pi/2-x+2npi)#, therefore
#cos(3x)=cos(pi/2-x+2npi)#
Since #costheta=cos("-"theta)#,
#3x=pi/2-x+2npi or 3x=("-"pi)/2+x-2npi#
Case 2.1: #3x=pi/2-x+2npi#
Add #x# to both sides
#4x=pi/2+2npi#
Divide both sides by #4#
#color(blue)(x=pi/8+(npi)/2,ninZZ)#
Case 2.2: #3x=("-"pi)/2+x-2npi#
Subtract #x# from both sides
#2x=("-"pi)/2-2npi#
Divide both sides by #2#
#color(blue)(x=("-"pi)/4-npi,ninZZ)#
Since #n# can be any integer, any term with #"-"n# can be replaced with #n#, so compiling everything gives
#color(red)({x:x={:(pi/4+npi),(("-"pi)/8+(npi)/2),(pi/8+(npi)/2),(("-"pi)/4+npi):},ninZZ})# or equivalently #color(red)({x:x=(npi)/8,n!=4m,ninZZ,m inZZ})#